Threatened endemic arthropods and vertebrates partition their diets with non‐native ants in an isolated island ecosystem - Maximillian P. T. G. Tercel; Jordan P. Cuff; William O. C. Symondson; Rosemary J. Moorhouse‐Gann; Tom Rhys Bishop; Nik C. Cole; Eric Jolin; Bethan Govier; Johannes Chambon; Rouben Mootoocurpen; Martine Goder; Ian P. Vaughan (Ecology, 2025)
The success of non‐native species depends on their ability to find food, which may ultimately lead to competition with native species and contribute to biodiversity loss in invaded ecosystems. Understanding which food resources are consumed is therefore crucial for evaluating how non‐native species mechanistically fit into native biological communities. Non‐native species may be predators or competitors of native species or may be consumed by native species as a novel source of nutrition, for example, and this can occur between both closely and distantly related species. Studies examining competitive interactions between non‐native species and distantly related native taxa are relatively rare, largely because it is difficult to compare their diets using traditional methods. However, dietary DNA metabarcoding overcomes these limitations by enabling the construction of highly detailed food webs. Here, we use dietary DNA metabarcoding between two generalist native consumers—a reptile (Telfair's skink) and a Scolopendra centipede (Serpent Island centipede)—and the hyperabundant non‐native ant community to test which consumer groups prey upon one another and partition food resources. To determine how non‐native ants fit into a native community, we calculated dietary composition, niche overlap, and dietary diversity of ants, centipedes, and skinks on Round Island, a small 2.19‐km 2 oceanic island located 22.5 km north‐east of Mauritius. We observed distinct partitioning of food resources among the three consumer groups—skinks, centipedes, and ants—and found that the level of predation between these groups varied. Skinks and centipedes frequently consumed non‐native ants, which may represent an important nutritional resource for both native consumers. Dietary differences persisted through seasons despite large shifts in the availability of food and concomitant diet composition for all three consumers. We conclude that non‐native ants fit into the biological community of Round Island as both prey for native consumers and extreme omnivorous generalists, but not necessarily at the expense of the native consumers because it is unlikely the consumers are competing for food resources. Our results suggest that abundant non‐native generalists, which are highly invasive in much of their introduced range, can infiltrate native food webs without exerting strong competitive forces on other common native generalist species.

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.